Is it possible to reduce loads of the locomotor system during the landing phase of dance figures? Biomechanical analysis of the landing phase in Grand Jeté, Entrelacé and Ballonné. - Gorwa, J.; Michnik, R. A.; Nowakowska, K.; Jurkojc, J.; Jochymczyk-Woniak, K. (Acta of Bioengineering and Biomechanics, 2019)
Purpose: The objective of the work was to determine biomechanical parameters influencing loads affecting the musculoskeletal system and shock absorption during the landing phase in Grand Jeté, Entrelacé and Ballonné. Methods: Motion kinematics measurements of the landing phase in GrandJeté, Entrelacé and Ballonné were carried out using the optical APAS system, and measurements of the GRF components - using Kistler platform. The research was carried out for three professional dancers. Kinematic and kinetic parameters of the landing were analysed. Results: The mean maximum GRF value in relation to the classical dancer amounted to 8.16 ± 1.37 N/BW. During landing, the joints of the lower limb are affected by external force moments of high values (ankle - 3.04 ± 0.54 [Nm/BW], knee - 7.56 ± 5.53 [Nm/BW], hip - 10.97 ± 6.80 [Nm/BW]). The maximum value of the external force moments in the joint were strongly negatively correlated with the value of the angle in the hip joint at the moment of the first contact with the ground. It was noticed that the obtainment of maxGRF was preceded by a decrease in kinetic energy of approximately 50%. Conclusions: Factors affecting loads present in the musculoskeletal system during the shock absorption of a leap are: GRF values, the values of external force generated inside the joints and a change in the value of kinetic energy. The safe shock absorption after landing is influenced by properly positioned limb at the moment of the first contact, a greater range of movements in the joints and longer time from the moment of the first contact to the obtainment of maxGRF.